Analysis of the changes in corneal optical density following small incision lenticule extraction for myopia and related influencing factors - Yifan Du; Yu Di; Shan Yang; Ying Li (Photodiagnosis and Photodynamic Therapy)
Purpose: To examine changes in corneal optical density (COD) following small incision lenticule extraction (SMILE) for myopia and the associated factors affecting COD. Methods: One hundred and ten eyes of 110 subjects who underwent SMILE were included in this study. COD and influencing factors were evaluated before and three months after SMILE. The changes in COD were compared and analysed with those of other influencing factors. Representative positive outcomes were chosen to investigate the influence in various ways. Results: This study found significant reductions in most anterior, central, and posterior CODs following SMILE (P<0.05), but the anterior 2–6 mm COD exhibited a significant increase (P<0.001). Lenticule thickness (LT), refractive sphere, preoperative Km, and Δcorneal volume (CV) were related to some of the whole ΔCODs (P<0.05). Age, gender, intraocular pressure (IOP), refractive cylinder, corrected distance visual acuity (CDVA), preoperative central corneal thickness (CCT), and preoperative CV were not correlated with the whole ΔCODs. Further exploration revealed that an increase in LT leads to a pattern of increasing and then decreasing changes in the whole ΔCODs. Most of the ΔCODs values were significantly lower in the high central corneal stromal ablation thickness group than in the high anterior corneal stromal ablation thickness group (P<0.05). Conclusions: Changes in COD were mainly caused by LT and its associated factors. However, the relationship between LT and ΔCOD might not be linear. Deeper corneal stromal ablation may reduce the COD. Changes in COD following SMILE are a multifaceted process influenced by various circumstances.